2011
DOI: 10.1016/j.acra.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Segmental Bronchoalveolar Lavage on Quantitative Computed Tomography of the Lung

Abstract: Rationale and Objectives With employment of both multi-detector computed tomography (MDCT) and endobronchial procedures in multi-center studies, effects of timing of endobronchial procedures on quantitative imaging (Q-MDCT) metrics is a question of increasing importance. Materials and Methods Six subjects were studied via MDCT at baseline, immediately following and at 4hrs and 24hrs post-BAL (right middle lobe (RML) and lingula). Through quantitative image analysis, non-air, or ‘tissue’ volume (TV) in each l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 22 publications
6
26
0
Order By: Relevance
“…The images were scored from 0 to 3 based on the previous veterinary and human data. In thoracic CT images, a score of 0 was equivalent to a normal thorax.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The images were scored from 0 to 3 based on the previous veterinary and human data. In thoracic CT images, a score of 0 was equivalent to a normal thorax.…”
Section: Methodsmentioning
confidence: 99%
“…Because it provides information on airway structure and lung parenchyma, CT use to investigate respiratory symptoms has been increasing in veterinary medicine . In human medicine, one study described evidence of thoracic radiographic changes following bronchoalveolar lavage, another on the effects of bronchoalveolar lavage on quantitative multi‐detector CT, and one on abnormalities on pulmonary ventilation/perfusion scans have been published . Those studies demonstrated that retained lavage fluid is correlated with lung opacity on immediate post‐bronchoalveolar lavage images, but resolved within 24 h. In veterinary medicine, only a few studies have observed the radiographic changes after lavage .…”
Section: Introductionmentioning
confidence: 99%
“…13,28 This study showed that patients with acromegaly have more lung mass than control subjects. Even more important, we observed that patients with active acromegaly have more lung mass in inspiratory CT than those with controlled acromegaly.…”
Section: 27mentioning
confidence: 98%
“…This method reflects tissue density accurately and estimates regional ventilation efficiently [5, 9]. Christensen et al and Reinhardt et al have estimated rates of local tissue deformation using a Jacobian-based ventilation measure [7, 10].…”
Section: Introductionmentioning
confidence: 99%